Atrial myxomas arise from multipotent cardiac stem cells. (24th April 2020) - Scalise, Mariangela; Torella, Michele; Marino, Fabiola; Ravo, Maria; Giurato, Giorgio; Vicinanza, Carla; Cianflone, Eleonora; Mancuso, Teresa; Aquila, Iolanda; Salerno, Luca; Nassa, Giovanni; Agosti, Valter; et al.
Abstract: Aims: Cardiac myxomas usually develop in the atria and consist of an acid-mucopolysaccharide-rich myxoid matrix with polygonal stromal cells scattered throughout. These human benign tumours are a valuable research model because of the rarity of cardiac tumours, their clinical presentation and uncertain origin. Here, we assessed whether multipotent cardiac stem/progenitor cells (CSCs) give rise to atrial myxoma tissue. Methods and results: Twenty-three myxomas were collected and analysed for the presence of multipotent CSCs. We detected myxoma cells positive for c-kit (c-kit pos ) but very rare Isl-1 positive cells. Most of the c-kit pos cells were blood lineage-committed CD45 pos /CD31 pos cells. However, c-kit pos /CD45 neg /CD31 neg cardiac myxoma cells expressed stemness and cardiac progenitor cell transcription factors. Approximately ≤10% of the c-kit pos /CD45 neg /CD31 neg myxoma cells also expressed calretinin, a characteristic of myxoma stromal cells. In vitro, the c-kit pos /CD45 neg /CD31 neg myxoma cells secrete chondroitin-6-sulfate and hyaluronic acid, which are the main components of gelatinous myxoma matrix in vivo . In vitro, c-kit pos /CD45 neg /CD31 neg myxoma cells have stem cell properties being clonogenic, self-renewing, and sphere forming while exhibiting an abortive cardiac differentiation potential. Myxoma-derived CSCs possess a mRNA and microRNA transcriptome overall similar to normal myocardium-derived c-kit pos /CD45 neg /CD31 neg CSCs, yet showing a relatively small and relevant fraction of dysregulated mRNA/miRNAs (miR-126-3p and miR-335-5p, in particular). Importantly, myxoma-derived CSCs but not normal myocardium-derived CSCs, seed human myxoma tumours in xenograft's in immunodeficient NOD/SCID mice. Conclusion: Myxoma-derived c-kit pos /CD45 neg /CD31 neg CSCs fulfill the criteria expected of atrial myxoma-initiating stem cells. The transcriptome of these cells indicates that they belong to or are derived from the same lineage as the atrial multipotent c-kit pos /CD45 neg /CD31 neg CSCs. Taken together the data presented here suggest that human myxomas could be the first-described CSC-related human heart disease.